Analysis of the Role of Transformational Leadership in Improving Employee Work Motivation and Performance and its Impact on Hospital Business Sustainability: JEL Classification: M12, M54, I11, I18, L25 - Yurita, Irma; Soekiswati, Siti; Ichsan, Burhannudin (Newinera Publisher, 2025)
This study aims to analyze the influence of transformational leadership on work motivation, employee performance, and business sustainability at Pala Raya Hospital (RSIA Pala Raya) in Tegal Regency, and to examine the mediating role of work motivation and employee performance in this relationship. The background of this study is based on the decline in patient visits and hospital revenue, which raises the need for a sustainability strategy based on internal organizational strengthening. The research method used is a quantitative explanatory approach with a total sampling technique of 200 employee respondents, and data analysis was conducted using SEM-PLS through SmartPLS 4.0. The results show that transformational leadership has a significant and positive effect on work motivation and employee performance, and has an impact on the sustainability of the hospital's business. Work motivation has a stronger influence than performance on sustainability. The mediation test shows that work motivation is a significant mediator in the relationship between transformational leadership and business sustainability, while employee performance is not. The study also identified various obstacles in the implementation of transformational leadership, such as lack of training, bureaucratic culture, and a reward system that does not support innovation. These findings emphasize the importance of the role of inspirational and participatory leadership in building motivation and supporting hospital sustainability.